Laparoscopic sterilization in HIV-1-positive women - Suwachai Intaraprasert (2018)
Laparoscopic sterilizations in HIV-1-positive women were performed. Patients who were HIV-1-positive underwent voluntary laparoscopic sterilization. The mean age of patients was 27.5 ± 3.8 years. Most were of low socioeconomic status. The mean duration of the operation was 14.4 ± 5.4 min. No accidental injury to the surgical team was recorded no complications occurred among the patients. It was concluded that laparoscopic sterilization in HIV-positive patients was safe with low risk of HIV transmission to the surgical team.